The Irish DNA Atlas: Revealing Fine-Scale Population Structure and History within Ireland. Issue 1 (December 2017) - Gilbert, Edmund; O'Reilly, Seamus; Merrigan, Michael; McGettigan, Darren; Molloy, Anne; Brody, Lawrence; Bodmer, Walter; Hutnik, Katarzyna; Ennis, Sean; Lawson, Daniel; Wilson, James; Cavalleri, Gianpiero
Abstract The extent of population structure within Ireland is largely unknown, as is the impact of historical migrations. Here we illustrate fine-scale genetic structure across Ireland that follows geographic boundaries and present evidence of admixture events into Ireland. Utilising the 'Irish DNA Atlas', a cohort (n = 194) of Irish individuals with four generations of ancestry linked to specific regions in Ireland, in combination with 2, 039 individuals from the Peoples of the British Isles dataset, we show that the Irish population can be divided in 10 distinct geographically stratified genetic clusters; seven of 'Gaelic' Irish ancestry, and three of shared Irish-British ancestry. In addition we observe a major genetic barrier to the north of Ireland in Ulster. Using a reference of 6, 760 European individuals and two ancient Irish genomes, we demonstrate high levels of North-West French-like and West Norwegian-like ancestry within Ireland. We show that that our 'Gaelic' Irish clusters present homogenous levels of ancient Irish ancestries. We additionally detect admixture events that provide evidence of Norse-Viking gene flow into Ireland, and reflect the Ulster Plantations. Our work informs both on Irish history, as well as the study of Mendelian and complex disease genetics involving populations of Irish ancestry.